2017
DOI: 10.1111/rode.12313
|View full text |Cite
|
Sign up to set email alerts
|

Natural Resource Revenues and Public Investment in Resource‐rich Economies in Sub‐Saharan Africa

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
(101 reference statements)
4
13
0
Order By: Relevance
“…Among the many studies on the effect of natural resource revenues on growth there are those (such as Sachs & Warner, 1995) who have indicated that these incomes have not been used for the economic development of developing countries. While other researches (such as Gylfason &Zoega, 2002 andKarimu et al, 2016) have found that natural resource revenues contribute to the economic growth of developing countries. However, all these researches did not investigate whether the natural resources rents have some impact on fiscal policy and capital formation of countries rich in natural resources.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Among the many studies on the effect of natural resource revenues on growth there are those (such as Sachs & Warner, 1995) who have indicated that these incomes have not been used for the economic development of developing countries. While other researches (such as Gylfason &Zoega, 2002 andKarimu et al, 2016) have found that natural resource revenues contribute to the economic growth of developing countries. However, all these researches did not investigate whether the natural resources rents have some impact on fiscal policy and capital formation of countries rich in natural resources.…”
Section: Introductionmentioning
confidence: 92%
“…However, in other hands, some studies found a positive effect of natural resources abundance on economic growth. For instance, Gylfason & Zoega (2002) and Karimu et al (2016) found a positive effect of natural resources rents on public investment which leads to economic growth. In order to provide the literature review about natural resources abundance, the fiscal policy and economic growth we create a table that shows theses empirical studies by date & authors, variables, methods and findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results suggest that in resource-rich developing countries, governments in resource-rich developing countries give little capital investment in priority sectors such as health, the same results were obtained by karimu and al. [14] and, Turan and Yankkaya [15].…”
Section: About the Rela-tionship Between Natural Resources And Health?mentioning
confidence: 99%
“…(This effect was not robust, however, to the addition of controls for initial income.) More recently, Karimu et al (2017) find resource rents (as a share of GDP) significantly improve public investment, though the strength of effect depends on institutional quality.…”
Section: Institutional Qualitymentioning
confidence: 99%
“…Channels proposed for the effect of resource dependence on a country's growth (historically developed for a resource curse) have included 1) crowding out of non-resource tradeable sectors that better aid growth in the long run, such as manufacturing (the "Dutch disease"), 2) depressing demand for education, 3) depressing institutional quality, and 4) providing perverse incentives regarding the quality of public spending (Bhattacharyya and Collier (2014); Collier and Goderis (2009); Karimu et al (2017)).…”
Section: Introductionmentioning
confidence: 99%